Impact Analysis On Perceived Credibility Of Online Job Advertisement And Employer Branding To Intention To Apply Generation Of Job Seekers With Organizational Attractiveness As Mediating Variable - Khairunnisa Della Egaputri; Aryana Satrya (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The current era of technological and industrial development 4.0 has had various impacts on daily life and activities, where the digitalization process has become the basis of competitiveness in the business and industrial environment. One of the areas that are affected is in the field of human resource management and the recruitment process which leads to electronic recruitment. Moreover, one of the challenges for companies today is facing a 'talent war' in the current labor market, which directs them to attract potential talent by creating employer branding and providing relevant vacancy information. This study examines the effect of perceived credibility of online job advertising and employer branding on the intention to apply for a job among Generation Z job seekers in technology start-ups in Indonesia, with organizational attractiveness as a mediating variable. The research respondents were 270 Generation Z job seekers in the Jabodetabek area, and a quantitative research method was used with Structural Equation Model (SEM) analysis